1999
DOI: 10.1002/hep.510300418
|View full text |Cite
|
Sign up to set email alerts
|

Role of thyroid hormone in stimulating liver repopulation in the rat by transplanted hepatocytes

Abstract: Recently, we reported near-complete repopulation of the rat liver by transplanted hepatocytes using retrorsine (RS), a pyrrolizidine alkaloid that alkylates cellular DNA and blocks proliferation of resident hepatocytes, followed by transplantation of normal hepatocytes in conjunction with two-thirds partial hepatectomy (PH). Because two-thirds PH is not feasible for use in humans, in the present study, we evaluated the ability of thyroid hormone (triiodothyronine [T 3 ]), a known hepatic mitogen, to stimulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 30 publications
(60 reference statements)
1
57
2
1
Order By: Relevance
“…27 Conversely, thyroxine administration to mice treated with phenytoin, rifampicin, and MCT accelerated liver repopulation, which was in agreement with the ability of thyroid hormone to stimulate hepatic DNA synthesis while promoting apoptosis in cells with genotoxic damage. 28,29 Taken together, these findings indicated that in mice exposed to phenytoin, rifampicin, and MCT, liver injury was age-dependent and gender-dependent, as shown here with 6-week-old to 8-week-old male mice. We used cell donors of 8 weeks' to 15 weeks' age for convenience; their age should have been immaterial unless aging-associated genetic lesions were to alter replication in healthy donor cells, which has not been shown.…”
Section: Discussionsupporting
confidence: 77%
“…27 Conversely, thyroxine administration to mice treated with phenytoin, rifampicin, and MCT accelerated liver repopulation, which was in agreement with the ability of thyroid hormone to stimulate hepatic DNA synthesis while promoting apoptosis in cells with genotoxic damage. 28,29 Taken together, these findings indicated that in mice exposed to phenytoin, rifampicin, and MCT, liver injury was age-dependent and gender-dependent, as shown here with 6-week-old to 8-week-old male mice. We used cell donors of 8 weeks' to 15 weeks' age for convenience; their age should have been immaterial unless aging-associated genetic lesions were to alter replication in healthy donor cells, which has not been shown.…”
Section: Discussionsupporting
confidence: 77%
“…13,26 However, more recently we observed as high as 15 to 20% repopulation in RS-treated female rats at 6 weeks after cell transplantation, in the absence of PH or any other exogenous stimulus. 20 Interestingly, both in the latter 20 and in the present study, cell transplantation was performed at 2 weeks after the second dose of RS, whereas in the first report, 13 this interval was 4 weeks.…”
Section: Dppivmentioning
confidence: 82%
“…Important from a human standpoint, such cells can be cryopreserved for up to 20 months with no loss of repopulating activity [50]. Many studies have also examined the transplantation potential of adult hepatocytes in the DPPIV − mutant rat, combining retrorsine treatment with a mitogenic stimulus, such as partial hepatectomy or triidothyronine (T3), leading to the rapid replacement of DPPIV − cells by DPPIV + donor cells [51,52]; even in the absence of a mitogenic stimulus, near-total replacement by donor cells occurs within 12 months [53].…”
Section: Mr Alison Et Almentioning
confidence: 99%